IGF‐II Promotes Stemness of Neural Restricted Precursors123. (15th May 2012) - Ziegler, Amber N.; Schneider, Joel S.; Qin, Mei; Tyler, William A.; Pintar, John E.; Fraidenraich, Diego; Wood, Teresa L.; Levison, Steven W.
Abstract: Insulin‐like growth factor (IGF)‐I and IGF‐II regulate brain development and growth through the IGF type 1 receptor (IGF‐1R). Less appreciated is that IGF‐II, but not IGF‐I, activates a splice variant of the insulin receptor (IR) known as IR‐A. We hypothesized that IGF‐II exerts distinct effects from IGF‐I on neural stem/progenitor cells (NSPs) via its interaction with IR‐A. Immunofluorescence revealed high IGF‐II in the medial region of the subventricular zone (SVZ) comprising the neural stem cell niche, with IGF‐II mRNA predominant in the adjacent choroid plexus. The IGF‐1R and the IR isoforms were differentially expressed with IR‐A predominant in the medial SVZ, whereas the IGF‐1R was more abundant laterally. Similarly, IR‐A was more highly expressed by NSPs, whereas the IGF‐1R was more highly expressed by lineage restricted cells. In vitro, IGF‐II was more potent in promoting NSP expansion than either IGF‐I or standard growth medium. Limiting dilution and differentiation assays revealed that IGF‐II was superior to IGF‐I in promoting stemness. In vivo, NSPs propagated in IGF‐II migrated to and took up residence in periventricular niches while IGF‐I‐treated NSPs predominantly colonized white matter. Knockdown of IR or IGF‐1R using shRNAs supported the conclusion that the IGF‐1R promotes progenitor proliferation, whereas the IR is important for self‐renewal. Q‐PCR revealed that IGF‐II increased Oct4, Sox1, and FABP7 mRNA levels in NSPs. Our data support the conclusion that IGF‐II promotes the self‐renewal of neural stem/progenitors via the IR. By contrast, IGF‐1R functions as a mitogenic receptor to increase precursor abundance. STEM CELLS 2012;30:1265–1276